Penegakan Hukum Terhadap Pelaku Pembakaran Hutan Dan Lahan Dikaitkan Dengan Teori Hukum Pancasila - Ridho Mubarak; Alvi Syahrin (Jurnal Ilmiah Penegakan Hukum, 2023)
The criminal act of burning forests and land which has sprung up in Indonesia has become an issue of environmental problems which is very worrying, this requires firm action from the government. Many parties, both individuals and legal entities (Corporations) who burn land aim to open new land without requiring much time and at a lower cost, this violates the values contained in Pancasila in the second precept because burning land with this aim is an act that civilized. The method used in this research is normative juridical, analytical descriptive in nature, using the Laws and Regulations approach. This research uses a statute approach, namely by collecting and analyzing statutory provisions related to the environment and corporations. The legal material collection technique used in this study was library research and then analyzed qualitatively. The results of the study show that Pancasila Legal Theory is a legal theory that is based on Pancasila values as its ontological, epistemological and even axiological basis where the development of national law has an identity and is sourced from Pancasila philosophy and values, so that Pancasila values are placed as ethical starting points and must animate national law. Against criminal acts of forest and land burning Behavior theory (behavior) emphasizes human motivation with an emphasis on the importance of cooperation through negotiations and technical support so that the industrial community is willing to take part in the compliance program. Personal relationship (personal relationship) between the object of regulation (regulated community) and government officials (regulator) as something that is very important and is a precondition for realizing conditions of obedience. This model views the industry as an incompetent or unknowledgeable regulatory object.